Disharmony of the Judiciary Authority against the Objects Execution of Sharia Economic Responsibility - Ngadi, Ronal (Damhil Law Journal, 2021)
Juridically the Court of Religion is a judicial institution that is authorized in examining, deciding and adjudicating and resolving the whole series of legal processes against disputes that occur in the field of sharia economy through the path of litigation (ordinary Court), including in executing the right of dependent objects of sharia economic cases that implementatively this is still a conflict or disharmony of authority between the judiciary rooted in the existence of conflict norms (ambivalence) contained in religious justice laws and sharia banking laws. In addition, the position of the contract or agreement also has consequences for the existence of the Court of Religion in the execution of the right of dependent objects of sharia economic cases, especially in the field of Sharia banking rooted in the unclear choice of the legal forum (choice of forum) contained in the agreement conducted by creditors (sharia banks) and debtors (customers), thus giving birth to bias and interpretation of multi-interpretation of the arising authority of other Courts which caused the Religious Court to lose its existence in resolving sharia economic disputes. Conflict or disharmony of authority that occurs between judicial institutions in the context of the execution of the right of sharia economic case dependent object in its implementation also provides legal implications for the position of debtors and creditors in the form of legal chaos (legal disorder) and legal confusion (confuse) in the community. It reflects the process of resolving cases that are counterproductive with legal certainty that is far from the principle of the simple justice system, fast and light costs and causes a decrease in the authority and credibility of the judiciary in the eyes of the public as an institution that carries out the duties of judicial power.